Use of Fermented Fish Ensilage in the Diets of Etroplus suratensis (Bloch) - N., Neethiselvan; G., Indira Jasmine; D., Manikandavelu; V.K., Venkataramani (Fishery Technology, 2025)
A feeding experiment was conducted to assess the ability of Etroplus sumtetisis (Bloch) to utilize diets containing fish ensilage as a major protein source. Attempt was also made to find out whether the neutralization of the fermented ensilage influenced the growth of Â£. suratensis or not. No significant difference in the survival rate of fish fed with various feeds was noticed (P(0.05). However, significant difference could be observed in specific growth rate,(P<0.01), food conversion efficiency and protein efficiency ratio (P<0.05). The study revealed that the diets containing fish ensilage, either neutralized with calcium hydroxide or without neutralization, could yield better weight gains (86.25% and 89.08% respectively) than other feeds. Â£. suratensis could utilize diets containing fish ensilage as the major source of protein for growth. While ensilage - based diet neutralized with sodium hydroxide recorded lower weight gains (80.87%) the effect was more adverse when potassium hydroxide was used as the neutralizing agent (56.18%).